Intensity gradients: A novel method for interpreting external loads in football - McGregor, R.; Anderson, L.; Weston, M.; Brownlee, T.; Drust, B. (International Journal of Sports Physiology and Performance, 2024)
Purpose Global navigation satellite system device-derived metrics are commonly represented by discrete zones with intensity often measured by standardizing volume to per-minute of activity duration. This approach is sensitive to imprecision in duration measurement and can lead to highly variable outcomes—transforming data from zones to a gradient may overcome this problem. The purpose of this study was to critically evaluate this approach for measuring team-sport activity demands.